2014
DOI: 10.1590/s1982-56762014000500008
|View full text |Cite
|
Sign up to set email alerts
|

Teratosphaeria pseudoeucalypti on eucalyptus in Brazil

Abstract: A new foliar disease caused by Teratosphaeria pseudoeucalypti on eucalyptus (E. globulus, E. urophylla x E. globulus and E. nitens x E. globulus) in Brazil is described. The disease is characterized by leaf spots of variable sizes and shapes, resulting in leaf blight and premature defoliation. Based on the morphological characteristics and multilocus phylogenetic analysis of the EF-1α, β-T and ITS-2 gene regions of five isolates, the fungus was identified as T. pseudoeucalypti. This is the first report of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The majority of these leaf associates cause leaf spots of minor importance. However, some, such as T. de structans, T. cryptica, T. nubilosa and T. pseudoeucalypti, are responsible for major economic losses to the forestry industry (Burgess and Wingfield, 2017;Cândido et al, 2014;Hunter et al, 2011). Surprisingly, DNA evidence has shown that the two stem canker pathogens are each more closely related to Eucalyptus leafassociated species than they are to each other (Quaedvlieg et al, 2014).…”
Section: R E L At I O N S H I P To E Uc a Ly P T U S L E A F Pat H O ...mentioning
confidence: 99%
“…The majority of these leaf associates cause leaf spots of minor importance. However, some, such as T. de structans, T. cryptica, T. nubilosa and T. pseudoeucalypti, are responsible for major economic losses to the forestry industry (Burgess and Wingfield, 2017;Cândido et al, 2014;Hunter et al, 2011). Surprisingly, DNA evidence has shown that the two stem canker pathogens are each more closely related to Eucalyptus leafassociated species than they are to each other (Quaedvlieg et al, 2014).…”
Section: R E L At I O N S H I P To E Uc a Ly P T U S L E A F Pat H O ...mentioning
confidence: 99%
“…All three taxa are known from diseased trees in eastern Australia plantations, but T. eucalypti and T. pseudoeucalypti are also known to cause disease problems beyond this range. For example, T. eucalypti is well -known in New Zealand (Hood et al 2002 ) and T. pseudoeucalypti is important pathogen in South America (Cândido et al 2014 ; Soria et al 2014 ; Ramos and Pérez 2015 ). In contrast, the four T. carnegiei strains included in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent to its description in 2010, T. pseudoeucalypti emerged in the neighbouring regions of Brazil (Cândido et al 2014 ), Uruguay (Soria et al 2014 ), and Argentina (Ramos and Perez 2015 ) in rapid succession. Although it was known in tropical and subtropical regions of eastern Australia, the South American hosts included temperate species such as E. globulus (Cerasoli et al 2016 ).…”
Section: Ima Genome-f 13ementioning
confidence: 99%